Proliferation of small arms and security dynamics in Kaduna State, Nigeria - Adamu, Waziri Rabiu (2020)
The proliferation of small arms has become a recognised security issue that needs to be responded to by various levels of authority given the fact that, small arms have recently become the most commonly used instruments for internal violence and criminal activities. The phenomenon has far-reaching effects on both human security and the state. Consequently, this study focuses on the menace of small arms; it particularly examines the political, security and socio-economic effects of the proliferation of small arms in Kaduna State, Nigeria using fragile state theory. This study employs qualitative research approach. Hence, techniques such as in-depth interviews and Focus Group Discussion (FGD) were utilised to collect primary data from four categories of participants that include the political figures, government security personnel, academicians and members of the civil societies. Meanwhile, books, journal articles, other printed materials and online sources served as secondary source of data. The data were analysed using thematic method of analysis. Thus, the research findings indicates that the proliferation of small arms has stirred a culture of violence in political undertakings; where arms are used in political activities. The menace threatens the governance thereby frustrating the effort to deal with the situation of conflict and criminal activities. The research findings also shows that the proliferation of small arms has created a sense of insecurity in Kaduna State. Within the socio-economic sphere, the study also reveals that societal settings have been badly affected. Similarly, social services and economic activities have been disrupted. Conversely, lack of political will, security network, poverty, and ethnoreligious conflict were found to be the determinants or reasons for the persistence of small arms proliferation in Kaduna State. The study recommends for serious commitment towards addressing security issues, political will on policy formation and implementation, reduction of poverty as well as collaboration with other stakeholders in order to address the issue of proliferation of small arms for a lasting security situation and peaceful political undertakings in the state and beyond.